Population dynamics of Green Tiger Shrimp (Penaeus semisulcatus) in the Persian Gulf (Bushehr Waters) - N. Niameimandi (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2000)
The population dynamics of Penaeus semisulcatus was studied out in the Persian (Bushehr province waters) through a series of research cruises conducted by the R/V Lavar. The growth and mortality parameters for both sexes were estimated by FLEFAN and FISAT computer programs. The following results obtained for males: L∞=37mm, K=1.8per year, t0=0.3, M=2.8, F=4.5 and Z = 7.3. These results for females were as follows: L∞=49 mm, K = 2.6 per year, t0=0.6, M=3.2, F=6.7, Z=9.9. According to obtained results, the exploitation rate for males and females were 0.61 and 0.67, respectively and the ϕ-value was estimated 7.8 for males and 8.3 for female. The sex ratio Was M:F-1:1 and the spawning season was from January to March with the main peak in January. The maximum age for males and females were determined 21 and 19 months respectively.